2012
DOI: 10.1371/journal.pgen.1002985
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Promote H3 Chromatin Integrity during Transcription Prevent Promiscuous Deposition of CENP-ACnp1 in Fission Yeast

Abstract: Specialized chromatin containing CENP-A nucleosomes instead of H3 nucleosomes is found at all centromeres. However, the mechanisms that specify the locations at which CENP-A chromatin is assembled remain elusive in organisms with regional, epigenetically regulated centromeres. It is known that normal centromeric DNA is transcribed in several systems including the fission yeast, Schizosaccharomyces pombe. Here, we show that factors which preserve stable histone H3 chromatin during transcription also play a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 61 publications
(103 reference statements)
11
118
1
Order By: Relevance
“…Indeed, spt16-22 and pob3-L78R cells exhibited partial sensitivity to CENP-A Cse4 overexpression (Fig. 1C,D), similar to findings in fission yeast (Choi et al 2012). However, we were unable to detect a significant change in CENP-A Cse4 stability in these mutants (data not shown), so additional mechanisms must contribute to the underlying synthetic sickness.…”
Section: Fact Has a Role In Cenp-a Cse4 Degradationsupporting
confidence: 83%
See 2 more Smart Citations
“…Indeed, spt16-22 and pob3-L78R cells exhibited partial sensitivity to CENP-A Cse4 overexpression (Fig. 1C,D), similar to findings in fission yeast (Choi et al 2012). However, we were unable to detect a significant change in CENP-A Cse4 stability in these mutants (data not shown), so additional mechanisms must contribute to the underlying synthetic sickness.…”
Section: Fact Has a Role In Cenp-a Cse4 Degradationsupporting
confidence: 83%
“…Although FACT could exclude CENP-A Cse4 from euchromatin by promoting H3 incorporation (Choi et al 2012), the association of FACT with Psh1 in coimmunoprecipitation experiments suggested a more direct role in CENP-A Cse4 degradation (Krogan et al 2002;Ranjitkar et al 2010). We therefore asked whether Psh1 directly interacts with FACT in vitro.…”
Section: The Spt16 Subunit Of the Fact Complex Interacts With Psh1mentioning
confidence: 98%
See 1 more Smart Citation
“…To test whether FACT-dependent recycling is required for histone conservation and H4K20 methylation, we determined the levels of H4K20me1 and H4K20me3 in cells with compromised Spt16. Using an earlier data set (Choi et al 2012), we confirmed that in very highly transcribed genes (more than 10 transcripts per cell), H3 occupancy is relatively low throughout the transcribed unit (Fig. 6A).…”
Section: Transcription-mediated Histone Conservation Allows For H4k20supporting
confidence: 68%
“…We omitted data from very highly expressed genes because low nucleosome occupancy confounds turnover measurement (note the seemingly low turnover at the NDR in Fig. 2F; Lee et al 2004;Choi et al 2012).…”
Section: Resultsmentioning
confidence: 99%